Kienlesberg Bridge in Ulm, Germany: The structural conception of a steel landmark in the context of a design tradition. Issue 2 (May 2017) - Akkermann, Jan; Halaczek, Bartlomiej; Vieth, Heinz‐Josef
Abstract: Kienlesberg Bridge is the new link for trams, pedestrians and cyclists between the inner city and the science centre in the north‐west of Ulm. The bridge crosses a railway junction near the main station and a new high‐speed rail link. The geometric boundary conditions lead to unequal spans and complex alignments. Therefore, the scheme that won the design competition, which is now under construction, proposed a bridge made of steel. The superstructure was designed as a semi‐integral continuous beam with main girders of varying depth. Owing to the pedestrian and cyclists' path on one side, the orthotropic plate cross‐section is asymmetric and the main girders have varying depths. Special calculations and details were necessary for dynamic and noise control reasons. The bridge is being built using incremental launching.